5-year outcomes of single iStent (G1) trabecular microbypass implantation with phacoemulsification in moderately advanced primary open angle glaucoma. - Ejaz Ansari (Public Library of Science (PLoS), 2021)
Purpose To evaluate the safety and efficacy of combined phacoemulsification and single iStent (G1) (iStent, Glaukos Corp. San Clemente, USA), implantation in moderately advanced primary open angle glaucoma (POAG) with 5-years follow-up. Methods Retrospective, interventional case series. All subjects had POAG and underwent single iStent implantation+ phaco+IOL by a single surgeon, with 5 years follow-up. Primary outcome measures: reduction in intraocular pressure (IOP) and proportion of eyes achieving at least 20% reduction of IOP at 5 years. Secondary outcome measures: number of glaucoma drops at 1 through to 5 years; change in visual field mean deviation (MD) at year 5 compared to baseline. Results 35 eyes of 26 patients were included. Mean (sd) medicated pre-op IOP was 18.5 (3.2) mm Hg on mean (sd) 2.3 (1.0) medications. Mean IOP was reduced to 15.9 (4.5) mm Hg on 2.2 (0.9) drops, 15.0mm (4.5) mm Hg on 2.3 (0.9) drops, 15.6 (3.6) mm Hg on 2.5 (1.0) drops, 15.7 (4.43) mmHg on 2.6 (1.0) drops and 14.7 (3.02) mmHg (P<0.001) on 2.7 (1.14) drops (P = 0.06) from 1 through to 5 years. At year 5, 62% of eyes had achieved at least 20% reduction in IOP. MD reduced from -8 (8.1) dB to -10.7 (13.4) dB over 5 years (p = 0.8) at 0.54dB/ annum. One eye required filtering surgery. There were no sight-threatening complications. Conclusion This study showed sustained IOP reduction and excellent safety profile for single iStent implantation. Uniquely it provides data for a more severe stage of glaucoma, and also visual field data, which indicated no significant change through 5 years.